Is the future of perioperative medicine created by "Cellular and Molecular Medicine"? - Ali Dabbagh (Journal of Cellular and Molecular Anesthesia, 2017)
During the last two decades, there was a growing approach towards role of perioperative medicine as "the future of anesthesia". Many practical and discipline activities were performed; including change in clinical practice and change in the name of departments to "Department of Anesthesia and Perioperative Medicine" or similar titles. These changes were based on a distinct logic: Anesthesia is not a spot or a brisk interval of care. Instead, it starts from "preoperative anesthesia care", goes to "intraopera tive anesthesia care" and leads to postoperative anesthesia care". This approach adapts more with improved clinical outcome